2018
DOI: 10.1029/2018wr022551
|View full text |Cite
|
Sign up to set email alerts
|

LSPIV Measurements of Two‐Dimensional Flow Structure in Streams Using Small Unmanned Aerial Systems: 2. Hydrodynamic Mapping at River Confluences

Abstract: Although past field work at stream confluences has relied on velocity information at specific cross sections to examine flow structure, detailed characterizations of spatial and temporal variations in the hydrodynamics of confluences are lacking. This study uses large‐scale particle image velocimetry (LSPIV) obtained from small unmanned aerial systems (sUAS), a method evaluated in a companion paper, to map surficial patterns of mean flow and turbulent structures at two small stream confluences in unprecedented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 53 publications
5
43
0
Order By: Relevance
“…As flow moves downstream, the separate high‐velocity cores of the incoming flows quickly merge into a single core. A region of flow separation develops along the left bank (right side of the cross section) downstream of a large bank protrusion on this side of the confluence (Figure 2; see also Lewis & Rhoads, 2018b). The pattern of secondary‐flow vectors reveals that pronounced counterclockwise helical motion develops over the middle part of the downstream channel in conjunction with curvature of flow from the Saline into the confluence.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As flow moves downstream, the separate high‐velocity cores of the incoming flows quickly merge into a single core. A region of flow separation develops along the left bank (right side of the cross section) downstream of a large bank protrusion on this side of the confluence (Figure 2; see also Lewis & Rhoads, 2018b). The pattern of secondary‐flow vectors reveals that pronounced counterclockwise helical motion develops over the middle part of the downstream channel in conjunction with curvature of flow from the Saline into the confluence.…”
Section: Resultsmentioning
confidence: 97%
“…More measurements of mixing rates and patterns at particular confluences over a suite of flow conditions are needed, and studies that assess mixing at numerous confluences are also recommended. Because of the difficulty in measuring detailed cross‐sectional velocities, studies that assess mixing at many confluences may benefit from remote sensing and noncontact methods to determines patterns of flow and mixing, at least at the surface (Biron et al, 2019; Lewis & Rhoads, 2018a, 2018b). However, as this study has shown mixing can be highly three‐dimensional, especially when influenced by helical motion of the flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A quantitative assessment of the LSPIV results provides insight into limiting factors of both sUAS and fixed systems, while examples and analyses of flow structure at river confluences demonstrate the utility of the method in highly complex flows. A companion study explores high‐resolution hydrodynamic mapping at river confluences, using results from this paper, to fundamentally improve understanding of these regions of complex 2‐D flow (Lewis & Rhoads, ). The results of this study help to better inform the value of LSPIV as a tool for measuring complex patterns of river flow in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The height of the flume walls was 40 cm. Different widths were employed for the upstream and downstream channels to mimic the channel expansion in recent confluence field studies (Biron et al, 2002; Boyer et al, 2006; Imhoff & Wilcox, 2016; Rhoads et al, 2009; Rhoads & Sukhodolov, 2001; Rhoads & Sukhodolov, 2008; Riley et al, 2015; Riley & Rhoads, 2012; Lewis & Rhoads, 2018; Sukhodolov et al, 2017; Sukhodolov & Sukhodolova, 2019). Two stacked tube grids were set behind the outlets of the upstream tanks in order to minimize the turbulence at the outlets.…”
Section: Methodsmentioning
confidence: 99%